Highly efficient acido-triggered reversible luminescent and nonlinear optical switch based on 5-π-delocalized-donor-1, 3-di(2-pyridyl)benzenes. Issue 28 (28th July 2015) - Nisic, Filippo; Colombo, Alessia; Dragonetti, Claudia; Fontani, Mattia; Marinotto, Daniele; Righetto, Stefania; Roberto, Dominique; Williams, J. A. Gareth
<x xml:space="preserve">Abstract</x> A highly efficient acido-triggered reversible luminescent and nonlinear optical switch based on 5-π-delocalized-donor-1, 3-di(2-pyridyl)benzenes is presented.